Medical treatment of Cushing’s disease with concurrent diabetes mellitus - Mehlich, Anna; Bolanowski, Marek; Mehlich, Dawid; Witek, Przemysław (Frontiers in Endocrinology, 2023)
Cushing’s disease (CD) is a severe endocrine disorder characterized by chronic hypercortisolaemia secondary to an overproduction of adrenocorticotropic hormone (ACTH) by a pituitary adenoma. Cortisol excess impairs normal glucose homeostasis through many pathophysiological mechanisms. The varying degrees of glucose intolerance, including impaired fasting glucose, impaired glucose tolerance, and Diabetes Mellitus (DM) are commonly observed in patients with CD and contribute to significant morbidity and mortality. Although definitive surgical treatment of ACTH-secreting tumors remains the most effective therapy to control both cortisol levels and glucose metabolism, nearly one-third of patients present with persistent or recurrent disease and require additional treatments. In recent years, several medical therapies demonstrated prominent clinical efficacy in the management of patients with CD for whom surgery was non-curative or for those who are ineligible to undergo surgical treatment. Cortisol-lowering medications may have different effects on glucose metabolism, partially independent of their role in normalizing hypercortisolaemia. The expanding therapeutic landscape offers new opportunities for the tailored therapy of patients with CD who present with glucose intolerance or DM, however, additional clinical studies are needed to determine the optimal management strategies. In this article, we discuss the pathophysiology of impaired glucose metabolism caused by cortisol excess and review the clinical efficacy of medical therapies of CD, with particular emphasis on their effects on glucose homeostasis.